2012
DOI: 10.1088/0022-3727/45/42/425302
|View full text |Cite
|
Sign up to set email alerts
|

Determining the nonparabolicity factor of the CdO conduction band using indium doping and the Drude theory

Abstract: Abstract. Due to their high intrinsic electron mobility, CdO-based materials are gaining interest as transparent conductive oxides. By creating model dielectric functions based on the Drude theory, accurate fits to the measured transmittance and reflectance of CdO and CdO:In thin-films were achieved without using a frequency dependent Drude damping parameter. Difference in the model between undoped and In-doped CdO showed that the Burstein-Moss shift is not the only mechanism which improves the transparency in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(90 citation statements)
references
References 39 publications
3
87
0
Order By: Relevance
“…It is extremely important to note that the Tauc relation assumes a parabolic conduction band. However, in our previous study, nonparabolicity of the conduction band in heavily doped arc-grown CdO films was clearly observed [37]. Therefore, the bandgap of CdO:In films is also calculated using the derivative of the transmittance spectra [38,39].…”
Section: Optical Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…It is extremely important to note that the Tauc relation assumes a parabolic conduction band. However, in our previous study, nonparabolicity of the conduction band in heavily doped arc-grown CdO films was clearly observed [37]. Therefore, the bandgap of CdO:In films is also calculated using the derivative of the transmittance spectra [38,39].…”
Section: Optical Propertiesmentioning
confidence: 95%
“…Based on Jain's model, in a heavily doped semiconductor, the bandgap renormalization can be described by [14,42] [21,22,37], the relative dielectric constant is 21.9 [43], and the values of Λ and N b are 1 [42]. The three terms in equation (6) represent the exchange energy of the majority carriers, the correlation energy, and the impurity interaction energy, respectively.…”
Section: Bandgap Shiftmentioning
confidence: 99%
“…For these CdO and CdO:In samples, ω p was obtained by simultaneously fitting the NIR transmittance and reflectance of each film, and n was taken from Hall measurements [10]. Using Pisarkiewicz's model [20], it has been observed that the nonparabolicity factor and the band edge effective mass of arc-grown CdO:In films are about 0.5±0.2 eV -1 and 0.16±0.05 m 0 , respectively [10]. The obtained values are in line with the results using the alpha approximation which was derived from Kane's two band k.p model [21].…”
Section: Theoretical Bandgap Calculationmentioning
confidence: 99%
“…Under most circumstances, it has been ignored that the Tauc relation is based on parabolic valence and conduction bands. As such, the Tauc relation is extensively misused to determine the optical bandgap in doped CdO since the conduction band exhibits clear nonparabolicity [4,5,10]. Thus, optical bandgaps obtained from Tauc plots may add controversy when studying the bandgap shift.…”
Section: Introductionmentioning
confidence: 99%
“…The measured transmittance spectra of films were fitted by the calculated transmittance from a dielectric model using Scout commercial software, which includes several built-in optical models [33][34][35]. An interband transition model of the absorption edge and the extended Drude free electron model for the free carriers were used, as applied previously for different doped ZnO thin films [30][31][32][33].…”
Section: Resultsmentioning
confidence: 99%